Poverty alleviation in Talok Village through Non-Formal Education Based on Bamboo Woven with Sustainable Development Methods Article 7 of Law No. 13 of 2011 to Sustainable Development Goals (SDGs) in Indonesia 2045 - Apriliani, Rintan Purnama Ayu (Universitas Negeri Semarang, 2018)
One of the objectives in Sustainable Development Goals (SDGs) is equitable education. Educational problems in developing countries, one of which in Indonesia, is the issue of access and opportunities to obtain education. In fact, education is one of the basic rights that must be fulfilled by the state. This paper will see alternative distribution of education through improving non-formal education in Talok Village, Tegal Regency, Central Java.